Health fraud against the elderly in China: the perspective of vulnerability manipulation - Zhou, You (Scams, cons, frauds, and deceptions, 2024)
The aging-related vulnerabilities have long been regarded as salient factors affecting older adults’ health fraud victimization. Traditional wisdom tends to focus on how victims’ vulnerability facilitates victimization. Despite its insights, such a focus neglects the importance of offenders’ active manipulation and exploitation of victims’ vulnerability, which may lead to victim blaming. Using data collected from 233 Chinese judgment documents (the court records of the crime) and 13 interviews with secondary victims – family members or close relatives of the (primary) victims, this paper examines how three aging-related vulnerabilities, declined ability in information processing, comfort-driven social preference, and positivity-driven emotional preference, were deliberately manipulated by health fraud offenders. This study provides the latest empirical evidence on how health fraud against the elderly occurs in China and sheds new light on vulnerability manipulation from the socio-emotional selectivity theory.